THE DEVELOPMENT OF SOCIAL PROBLEMS OF ENLIGTENMENT ACTIVITIES IN THE FIELD OF EDUCATION OF ADULTS - Folvarochnyi, Ihor (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the historical and pedagogical issues of educational activities in the field of education of adults. This article gives much attention to the social problematics of the subject (the problem of human’s social protection, the necessity of a systematic solution of a range of socially-oriented issues in the education sphere, the focus of the social educational work’s vector of in the field of non-formal education of adult).